2020
DOI: 10.1021/acs.jproteome.9b00838
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis Revealed the Importance of Inflammation-Mediated Downstream Pathways and the Protective Role of Curcumin in Bleomycin-Induced Pulmonary Fibrosis in C57BL/6 Mice

Abstract: Bleomycin (BLM)-induced pulmonary fibrosis is characterized by inflammation in the alveoli, subsequent deposition of extracellular matrix (ECM) and myofibroblasts, and an impaired fibrinolytic system. Here, we describe major hematological changes, the IL-17A-mediated p53-fibrinolytic pathway, and the high throughput hits of liquid chromatography−mass spectrometry (LC−MS) analysis during the progression of pulmonary fibrosis and the therapeutic potential of curcumin against disease progression. C57BL/6 mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The BLM stimulates the expression of of IL‐17A, induces the phosphorylation of tumor suppressor protein (Tp53), Mapk1/3, and upregulation of mechanistic target of rapamycin ( Mtor ), plasminogen activator, urokinase ( Plau ), PLAU receptor ( Plaur ), serpin family E member 1 ( Serpine 1), smooth muscle aortic alpha‐actin 2 ( Acta 2), cleaved cysteine‐aspartic acid protease 3 (cleaved Casp 3), marker of proliferation Ki‐67 ( MKI 67), and proteins including annexin A6 (Anxa6), proteasome 26S Subunit, ATPase 6 (Psmc6), alcohol dehydrogenase (Adh1), copine 1 (Cpne1), hemoglobin subunit beta‐H1 (Hbb‐bh1), UDP‐Glucose glycoprotein glucosyltransferase 1 (Uggt1), growth associated protein 43 (Gap43), superoxide dismutase 2 (Sod2), heat shock protein family 1B (Hspa1b), protein phosphatase 1 regulatory inhibitor subunit 14B (Ppp1r14b), bleomycin hydrolase (Blmh), antioxidant 1 copper chaperone (Atox1), hemoglobin subunit‐beta‐2 (Hbb‐b2), Ras‐related protein Rab‐10 (Rab10) and downregulation of Hbb‐b1, transcription factor p65 (Rela), neutrophilic granule protein (Ngp), paraoxonase 3 (Pon3), high mobility group box protein 1 (Hmgb1), and hypoxia up‐Regulated 1 (Hyou1), which are involved in response to a stimulus; increased expression of inflammation‐related proteins such as Acta2, Ras‐related protein R‐Ras2 (Rras2), actin related protein 2/3 complex subunit 2 (Arpc2), G Protein subunit gamma 12 (Gng12), Ras homolog family member A (RhoA), phospholipase C eta 1 (Plch1), signal transducer and activator of transcription 1 (Stat1), Rac family small GTPase 1 (Rac1), Arpc3, P21 (RAC1) activated kinase 3 (Pak3), myosin light chain kinase (Mylk), cell division control protein 42 homolog (Cdc42), Arpc5, protein kinase CAMP‐activated catalytic subunit beta (Prkacb) and downregulation of Rela and complement component C7 (C7) (Gouda et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The BLM stimulates the expression of of IL‐17A, induces the phosphorylation of tumor suppressor protein (Tp53), Mapk1/3, and upregulation of mechanistic target of rapamycin ( Mtor ), plasminogen activator, urokinase ( Plau ), PLAU receptor ( Plaur ), serpin family E member 1 ( Serpine 1), smooth muscle aortic alpha‐actin 2 ( Acta 2), cleaved cysteine‐aspartic acid protease 3 (cleaved Casp 3), marker of proliferation Ki‐67 ( MKI 67), and proteins including annexin A6 (Anxa6), proteasome 26S Subunit, ATPase 6 (Psmc6), alcohol dehydrogenase (Adh1), copine 1 (Cpne1), hemoglobin subunit beta‐H1 (Hbb‐bh1), UDP‐Glucose glycoprotein glucosyltransferase 1 (Uggt1), growth associated protein 43 (Gap43), superoxide dismutase 2 (Sod2), heat shock protein family 1B (Hspa1b), protein phosphatase 1 regulatory inhibitor subunit 14B (Ppp1r14b), bleomycin hydrolase (Blmh), antioxidant 1 copper chaperone (Atox1), hemoglobin subunit‐beta‐2 (Hbb‐b2), Ras‐related protein Rab‐10 (Rab10) and downregulation of Hbb‐b1, transcription factor p65 (Rela), neutrophilic granule protein (Ngp), paraoxonase 3 (Pon3), high mobility group box protein 1 (Hmgb1), and hypoxia up‐Regulated 1 (Hyou1), which are involved in response to a stimulus; increased expression of inflammation‐related proteins such as Acta2, Ras‐related protein R‐Ras2 (Rras2), actin related protein 2/3 complex subunit 2 (Arpc2), G Protein subunit gamma 12 (Gng12), Ras homolog family member A (RhoA), phospholipase C eta 1 (Plch1), signal transducer and activator of transcription 1 (Stat1), Rac family small GTPase 1 (Rac1), Arpc3, P21 (RAC1) activated kinase 3 (Pak3), myosin light chain kinase (Mylk), cell division control protein 42 homolog (Cdc42), Arpc5, protein kinase CAMP‐activated catalytic subunit beta (Prkacb) and downregulation of Rela and complement component C7 (C7) (Gouda et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, IL-17A research has led to the discovery of its potential as a therapeutic target for various forms of inflammation and autoimmune disorders (Kuwabara et al 2017;McGeachy et al 2019). In the current study, we developed a resource of signaling events mediated by IL-17A/ IL-17RA signaling by excerpting all research articles from the literature and compiling them in similar lines to earlier reports on comprehensive signaling maps including IL-33, IL-18 and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), C-C motif chemokine ligand 18 (CCL18) (Pinto et al 2018;Rex et al 2020Rex et al , 2021Aravind et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Wu Q et al suggests that p53 may be an important gene in the occurrence and progression of PF by regulating EMT, senescence, apoptosis, and other cellular processes [ 48 ]. Some researchers believe that the expression of p53 is upregulated in IPF [ 49 , 50 ]. However, Wang m et al found that the p53 protein expression was significantly downregulated in BLM-induced PF mice and could be upregulated by astaxanthin intervention [ 51 ].…”
Section: Discussionmentioning
confidence: 99%